The use of visual, auditory, kinesthetic (VAK) learning to increase student learning outcomes - Rosdiana, Muspratiwi Pertiwi Muslimin; Muslimin, Muslimin; Firmansyah, Firmansyah (Inornatus: Biology Education Journal, 2022)
This study uses classroom action research. The research objective is to apply the visual, auditory, kinesthetic (VAK) learning model to improve student learning outcomes. The subjects in this study were teachers and students of grade IV primary school totaling 24 students. Data collection techniques used are observation, tests, and documentation. Actions have been done as much as 2 cycles. Data is calculated using percentages. The findings reveal that the learning outcomes of cycle I are in the sufficient category, and there is an increase in cycle II which is in the good category. The conclusion in this study is that the application of VAK learning can improve the learning process and student science learning outcomes.